2006
DOI: 10.1002/bsl.738
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐arrest diversion of people with mental illness: literature review and international survey

Abstract: Mental health diversion is a process where alternatives to criminal sanctions are made available to persons with mental illness (PMI) who have come into contact with the law. One form of mental health diversion is pre-arrest, in which the police use their discretion in laying charges. Concomitant with the growth of pre-arrest diversion programs is a growing body of research devoted to the phenomenon. The purpose of this paper is to review the existing literature of pre-arrest diversion, and to report the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…by requiring adherence to a mental health treatment plan as an alternative to serving a prison sentence (Goodale, Callahan et al 2013). Crisis interventions teams are teams of law enforcement officers, sometimes paired with mental health professionals, who have completed training on the symptoms of mental illness, mental health treatment, and de-escalation techniques (Hartford, Carey et al 2006, Watson and Fulambarker 2012). These teams are responsible for responding to law enforcement calls involving individuals with SMI, with the goal of preventing violent encounters with law enforcement caused by psychiatric symptoms such as hallucinations or delusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by requiring adherence to a mental health treatment plan as an alternative to serving a prison sentence (Goodale, Callahan et al 2013). Crisis interventions teams are teams of law enforcement officers, sometimes paired with mental health professionals, who have completed training on the symptoms of mental illness, mental health treatment, and de-escalation techniques (Hartford, Carey et al 2006, Watson and Fulambarker 2012). These teams are responsible for responding to law enforcement calls involving individuals with SMI, with the goal of preventing violent encounters with law enforcement caused by psychiatric symptoms such as hallucinations or delusions.…”
Section: Introductionmentioning
confidence: 99%
“…These teams are responsible for responding to law enforcement calls involving individuals with SMI, with the goal of preventing violent encounters with law enforcement caused by psychiatric symptoms such as hallucinations or delusions. Some teams coordinate with mental health clinics or psychiatric crisis response teams in order to further divert individuals with SMI away from criminal justice involvement and into treatment (Hartford, Carey et al 2006, Watson and Fulambarker 2012, Kennedy-Hendricks, HA et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This model is the most popular of the alternative models (Hartford et al, 2006). Officers who volunteer to participate in the program receive 40 hr of training in mental health issues, substance abuse, and legal issues.…”
Section: Models Of Police Responsementioning
confidence: 99%
“…Officers are dispatched to mental health disturbance calls and respond alongside mental health professionals. Both the officers and mental health professionals decide on the appropriate course of action (Hartford, Carey, & Mendonca, 2006).…”
Section: Models Of Police Responsementioning
confidence: 99%
“…A literature review of prebooking diversion programs for people with mental illness identified specific program elements that improve processes and outcomes: ongoing interagency coordination between law enforcement and behavioral health, a single liaison person, and an emergency drop-off center (49). For people with low-level drug offenses, prebooking diversion models have only recently begun to develop in the United States; evidence from the first program site, in Seattle, indicates effectiveness for reducing recidivism (26).…”
Section: Interventions To Prevent Jail and Prison Stays By Diverting mentioning
confidence: 99%